Implementasi Komunikasi Korporat dalam Transformasi Perusahaan: Studi Kasus: PT Produksi Film Negara (Persero) - Rori Hastomo; Rahma Sinatrya Fatmawati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study examines the implementation of corporate communication in the organizational transformation of PT Produksi Film Negara (Persero) (PFN), a state-owned film company in Indonesia. The transformation represents a strategic initiative to address financial challenges and enhance the company’s relevance in the national film industry by repositioning its role from a film production house to a film financing institution. This shift in the business model requires effective internal communication to ensure that all employees understand, embrace, and support the new direction of the company, while fostering a work culture that is adaptive to the dynamics of the modern film market. Externally, the corporate communication strategy is aimed at reintroducing PFN to stakeholders, including investors, filmmakers, and the media, through consistent and targeted messaging. Such efforts are expected to build PFN’s new reputation as a credible financial entity, attract potential partners, and restore public trust that had declined due to operational limitations over the past decades. This study employs a qualitative approach, using in-depth interviews, participatory observations, and document analysis as data collection techniques. The findings reveal that corporate communication plays a central role in reducing internal resistance and fostering strategic relationships with external stakeholders, which ultimately becomes a decisive factor in PFN’s success in realizing its vision as a film financing company